2019
DOI: 10.1186/s12914-019-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health insurance status among migrants from sub-Saharan Africa on access to health care and HIV testing in Germany: a participatory cross-sectional survey

Abstract: Background Among all newly diagnosed HIV cases in Germany in 2015, 16% originated from sub-Saharan Africa. Twelve percent of these infections were contracted within Germany and migrants from sub-Saharan Africa (misSA) are diagnosed later than Germans. Migrants, specifically those without health insurance, face many barriers accessing health care due to their residence status and cultural, socio-economic, legal and linguistic barriers. We assessed whether misSAs’ access to healthcare and utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
3
25
1
Order By: Relevance
“…Social insurance policies to increase public access to health care facilities have also been adopted by other countries. The results of studies evaluating this matter show positive results [51][52][53], although also in the implementation there were still some obstacles encountered [54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Social insurance policies to increase public access to health care facilities have also been adopted by other countries. The results of studies evaluating this matter show positive results [51][52][53], although also in the implementation there were still some obstacles encountered [54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, just like the US, both public resources and private health insurance offers coverage for citizens living with HIV [33,34]. However, migrants in Europe have to contend with social and structural barriers to access to care when diagnosed with HIV [35,36]. In sub-Saharan Africa, different studies have looked at the financial sustainability of HIV/AIDS and universal health coverage (UHC) programs [37], how to expand private health insurance coverage for HIV and AIDS [38], and considerations in the integration of the global HIV/AIDS response into UHC [39].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in several countries on the impact of ownership of health insurance have found findings that have increased the use of health services that is far better (Lee et al, 2018) (Tilahun et al, 2018) (Miraldo, Propper and Williams, 2018) (Müllerschön et al, 2019). The same conditions apply to Indonesia (Mubasyiroh, Nurhotimah and Laksono, 2016) (Laksono, Wulandari and Soedirham, 2019b).…”
Section: Discussionmentioning
confidence: 92%